Exploring Character Education in 'Bocah-Bocah Borneo': Implications for Student Character Development - Monika, Marisa; Wati, Unik Ambar (AL-ISHLAH: Jurnal Pendidikan, 2024)
Literature is an integral part of character formation efforts. This research aims to determine the contribution of the short story anthology book ‘Bocah-Bocah Borneo’ by Neneng Eliana to the character education of elementary school students. The research method used is inferential content analysis in the form of a process of describing, classifying, interpreting, and concluding the character values contained in the short story and implications for student character development based on Strengthening Ki Hajar Dewantara's Character Education. The data sources for content analysis included the short story anthology 'Bocah-Bocah Borneo', presidential regulations related to Strengthening Character Education inspired by Ki Hajar Dewantara's philosophy, and relevant articles from accredited scientific journals.". "The content analysis involved systematically procuring data from the short story anthology, reducing and categorizing the data, making inferences, and conducting a detailed analysis. The results of the data analysis show several findings. First, there are eighteen characters values contained in the short story anthology ‘Bocah-Bocah Borneo’, namely religious, brave, socially caring, environmentally caring, friendly and communicative, responsible, curious, disciplined, hard-working, polite, independent, honest, tolerant, creative, democratic, spirit of nationality, patriotism, and appreciate for achievements. Second, the implications for student character development of ‘Bocah-Bocah Borneo’ short story which originates from the five values of Strengthening Character Education from Ki Hajar Dewantara's philosophy, namely: religion, nationalism, independence, cooperation, and integrity. This research concludes that the short story contributes significantly to the character instruction values of elementary school understudies.